The user behavior observation for wayfinding in the built environment (Estudos em Design, 2015)
This study introduces a systematic overview of user behavior observation when confronted with the user´s task of moving around in a built environment. The observation framework is based on "what" and "how" to observe. It includes a literature review about user wayfinding behavior as the basis for the categorization of observable behaviors. Spatial behavior mapping technique is proposed for behavior observation/registration. This technique sets the way to observe user behavior during his/her navigation and to log data on the performance of environmental information.
Keywords: Ergonomics of de built environment; wayfinding; user